A Combined Discrete Event, Agent - Based Approach to Modeling the Tensile Strength of One - Dimensional Fibrous Materials: Part 1: Simulations based on fiber slippage. Issue 4 (December 2014) - Cherkassky, Arkady; Bumagin, Eugene
This paper presents a new approach to predict the tensile strength of one-dimensional fibrous materials. The approach combines discrete-event simulation of the fiber flow with agent-based modelling of the fiber slippage. The ability of the elaborated model of the fiber flow to track every fiber separately enables the calculation and analysis of all contacts and forces between the fibers, and the prediction of the material's tensile strength. The model is based on the phenomenon of the strength associated with the fiber slippage effect. Algorithms for modeling the cross-section and the segment tensile strength are developed. Implementation of this algorithm and the study of the behavior of the elaborated model by varying the basic parameters will be described in the Part 2 of the article.